1996
DOI: 10.3109/02841869609109921
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity of Mesothelioma Cell Lines

Abstract: The present study was carried out in order to examine the radiosensitivity of malignant pleural mesothelioma cell lines. Cell kinetics, radiation-induced delay of the cell cycle and DNA ploidy of the cell lines were also determined. For comparison an HeLa and a human foetal fibroblast cell line were simultaneously explored. Six previously cytogenetically and histologically characterized mesothelioma tumor cell lines were applied. A rapid tiazolyl blue microtiter (MTT) assay was used to analyze radiosensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…Although radiation therapy has shown efficacy on mesothelioma cell lines [77], it has proven disappointing in mesothelioma patients and poor results have been described in several series [78,79]. One of the major problems in performing radiation therapy is determining the volume of the target area, which includes the diaphragm, mediastinum, and chest wall and excludes the lung.…”
Section: Radiation Therapymentioning
confidence: 99%
“…Although radiation therapy has shown efficacy on mesothelioma cell lines [77], it has proven disappointing in mesothelioma patients and poor results have been described in several series [78,79]. One of the major problems in performing radiation therapy is determining the volume of the target area, which includes the diaphragm, mediastinum, and chest wall and excludes the lung.…”
Section: Radiation Therapymentioning
confidence: 99%
“…We have there-fore used two endpoints to evaluate radiation sensitivity: the clonogenic survival assay and the MTT assay, both of which have been used successfully for assessment of radiosensitivity for in vitro cell lines [37][38][39][40]. The radiobiological parameters examined were the surviving fraction of cells treated with 2 Gy radiation (SF 2 ), the surviving fraction of cells treated with 8 Gy radiation (SF 8 ), and the values for ␣ and ␤, estimated from the linearquadratic model.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in radiosensitivity were best distinguished by comparison of SF 2 values. Hakkinen et al (31) found significant differences in radiosensitivity between mesothelioma cell lines from different patients as expressed by the survival fractions at SF 2 or by the initial shape of the survival curve, a. In three mesothelioma cell lines derived from our patients the .…”
Section: Eschwege Et Al (1 8)mentioning
confidence: 99%